Frustrated Lewis pairs on nanoparticles for colloidal catalysis: dream or reality? - Carenco, Sophie (Comptes Rendus. Chimie)
Catalysis by the colloidal suspension of nanoparticles has attracted considerable attention in recent years as it may combine interesting features: (i) the possibility of using inorganic catalysts, such as those of transition metal nanoparticles; (ii) the opportunity of adding well-designed ligands, as in homogeneous catalysis, to tune the activity and selectivity of a given reaction. However, it is critical to delineate operating conditions (e.g., stoichiometry of the ligand versus the number of active surface sites) for which the catalyst surface does not get poisoned by a very large number of coordinating species.Originating from molecular catalysis, a frustrated Lewis pair (FLP) is a compound containing a strong Lewis acid and a strong Lewis base that are prevented from forming an adduct. The FLPs represent a major advance over the past 20 years for the catalytic activation of small molecules (H2, CO, CO2, etc.) under mild conditions. More recently, a similar interaction on the surface of inorganic compounds has enabled hydrogenation to be carried out under milder conditions than those in conventional processes. These surface FLPs are emerging as promising materials in heterogeneous catalysis, but they remain underdeveloped in the field of transition metal nanoparticles.Here, we propose and illustrate the design of metal nanoparticles in colloidal suspension as Lewis acid partners of a “NanoFLP”, that is, a frustrated Lewis pair in which one partner is the nanoparticle surface and the other is a molecular Lewis base. This concept was explored for the hydrogenation of alkynes such as phenylacetylene. However, to this date, no direct proof for the occurrence of an FLP has been provided on the examples that we developed. We discuss possible interpretations of the experimental data and ways of clarifying the mechanism involved.